A genetic study of SSV1, the prototypical fusellovirus - Iverson, Eric; Stedman, Kenneth (Frontiers in Microbiology, 2012)
Viruses of thermophilic Archaea are unique in both their structures and genomic sequences. The most widespread and arguably best studied are the lemon-shaped fuselloviruses. The spindle-shaped virus morphology is unique to Archaea but widespread therein. The best studied fusellovirus is SSV1 from Beppu Japan, which infects Sulfolobus solfataricus. Very little is known about the function of the genes in the SSV1 genome. Recently we have developed genetic tools to analyze these genes. In this study, we have deleted three SSV1 open reading frames ranging from completely conserved to poorly conserved: VP2, d244, and b129. Deletion of the universally conserved ORF b129, which encodes a predicted transcriptional regulator, results in loss of infectivity. Deletion of the poorly-conserved predicted DNA binding protein gene VP2 yields viable virus that is indistinguishable from wild-type Deletion of the well-conserved ORF d244 that encodes a predicted nuclease yields viable virus. However infection of Sulfolobus solfataricus with virus lacking ORF d244 dramatically retards host growth, compared to the wild-type virus.